Peran Pendidikan Agama Islam Dalam Membentuk Karakter Siswa Diera Modernisasi - Triyanto, Agus; Ramly, Amir Tengku (Diversity: Jurnal Ilmiah Pascasarjana, 2022)
The results of this study indicate that the role of Islamic religious education in shaping student character is carried out through activities that shape the personality of students to be brave and independent such as: (1) Intra-curricular activities or KBM, in this activity the teacher instills character in the process of teaching and learning activities from all eyes. religious lessons such as Aqidah Akhlak, at-Tawhid, al-Qur’an Hadith, Islamic history, Fiqh, and Arabic. Every teacher must reflect good character and be a good role model. (2) Extracurricular activities which include: Muhadharah (speech), Tilawatil Qur’an, Sports, Calligraphy and Hadrah, in these student activities for tawadhu, honest, trustworthy, responsible, self-respect, respect for achievement, religious and hard work. (3) Dormitory Activities, these activities are carried out outside of KBM and extracurricular hours such as cleaning the bathroom, tidying the bed, working together, picket dormitory etc. This activity instills in students to be more independent, helps others, cares about the environment and cleanliness, is formed like a small community. Thus students are educated to grow to have character, because with that students are ready to face life in the modernization era